Policy Analysis of the Occupational Safety and Health Management System of SMK3 at the North Sumatra Provincial Employment Supervision UPTD - Sinaga, Antonius; Ritonga, Syafruddin; Lubis, Maksum Syahri (Universitas Medan Area, 2025)
This study aims to analyze the policies of the Occupational Safety and Health Management System (SMK3) implemented in the North Sumatra Provincial Manpower Supervision UPTD. A qualitative approach is used to explore the effectiveness of policies, implementation challenges, and their impact on occupational safety. Data were obtained through in-depth interviews, field observations, and document analysis. The results of the study show that the SMK3 policy has positively impacted reducing the number of work accidents, especially in companies that consistently implement safety standards. However, its implementation is still constrained by limited resources, a low understanding of small and medium enterprises (SMEs) regulations, and a lack of labor participation in several companies. Management commitment and occupational safety culture have proven to be key factors in successfully implementing SMK3. In addition, digital technology has begun to support supervision, although it still requires development. This study recommends increasing the capacity of supervisors, more intensive policy socialization, and collaboration with K3 training institutions. With a more inclusive and technology-based approach, the SMK3 policy is expected to improve overall occupational safety in North Sumatra Province.